Enhancing Employee Performance through Leadership, Loyalty, and Job Satisfaction: A Study at PT XYZ Palembang, Indonesia - Muhammad Dzikri; Tobari, Tobari; Hustia, Anggreany; Nemanja Karapavlović; Voinea Cristina Maria; Monzer Mohamed Ali Mohamed; Idris Sani; Abdulkadir Khalif; Nguyen Viet Ha (International Journal of Management Science, 2024)
This study aims to determine the effects of leadership, loyalty, and job satisfaction on employee performance at PT XYZ Palembang. The research type employed is associative research. The research population consists of 100 employees, with a sample of 50 employees. Data collection was conducted using questionnaires. Multiple linear regression analysis was utilized for data analysis, along with hypothesis testing using the F test and t test. The results of the study indicate the following: 1) Leadership, loyalty, and job satisfaction collectively have a positive and significant impact on employee performance at PT XYZ Palembang. 2) Leadership has a positive and significant influence on employee performance at PT XYZ Palembang. 3) Loyalty does not have a significant effect on employee performance at PT XYZ Palembang. 4) Job satisfaction has a positive and significant effect on employee performance at PT XYZ Palembang. These findings suggest that enhancing leadership and job satisfaction can significantly improve employee performance, highlighting the need for targeted managerial strategies.